2023
DOI: 10.3390/polym15214305
|View full text |Cite
|
Sign up to set email alerts
|

FDM 3D Printing and Properties of PBS/PLA Blends

Wangwang Yu,
Liwei Sun,
Mengya Li
et al.

Abstract: Poly(lactic acid) (PLA) and Poly(butylene succinate) (PBS) were chosen as raw materials and melt blended by a twin screw extruder and pelletized; then, the pellets were extruded into filaments; after that, various PBS/PLA blending samples were prepared by Fused Deposition Molding (FDM) 3D printing technology using the filaments obtained and the effect of the dosage of PBS on technological properties of 3D-printed specimens was investigated. For comparison, the PLA specimen was also prepared by FDM printing. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Moreover, we once investigated the thermal stability of FDM 3D-printed PBS/PLA samples and found that the thermal stability of the PBS/PLA blends would be worsened when more dosage of PBS was incorporated [ 34 ]. The improved thermal stability of FDM 3D-printed PBAT/PLA blends indicated that the PBS/PLA blends can be replaced with the PBAT/PLA blends when the thermal stability of the samples is taken into consideration.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we once investigated the thermal stability of FDM 3D-printed PBS/PLA samples and found that the thermal stability of the PBS/PLA blends would be worsened when more dosage of PBS was incorporated [ 34 ]. The improved thermal stability of FDM 3D-printed PBAT/PLA blends indicated that the PBS/PLA blends can be replaced with the PBAT/PLA blends when the thermal stability of the samples is taken into consideration.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the impact strength data (Figure 15) for the vPLA:PC-PLA (50:50) blended specimens with those of 100% rPLA and 100% vPLA [46] showed that the vPLA:PC-PLA (50:50) blended specimens exhibited a 9.15% higher impact strength than the rPLA samples and approximately similar impact strength to the vPLA specimens when printed at a larger layer height and high infill (experimental runs 9). The impact test results showed that when vPLA was incorporated into PC-PLA, it acted as the centre of the built-in stress, resulting in an increased capacity for absorbing energy during the impact test and enhancing the impact strength [85]. In addition, owing to the increase in infill density, the interlayer adhesion between two consecutive layers increases, which improves the impact strength [86,87].…”
Section: Impact Behaviourmentioning
confidence: 99%
“…The tensile test results also demonstrated low impact strength for the smaller layer height specimens printed at low-temperature (Figure 11). These defects originated from the poor interfacial bonding between vPLA and PC-PLA at lower nozzle temperature and layer height, which might have reduced the impact strength [84,85]. In addition, a lower layer height results in a higher number of bonding lines between the layers, which leads to a higher probability of void formation.…”
Section: Impact Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the HKUST−1's crystalline structure, morphology, and textural properties, as well as CO 2 /CH 4 adsorption capacities, were preserved in the synthesized HKUST−1/PLA composite when compared to the pristine HKUST−1. However, the moisture stability was not significantly improved in comparison to the pristine HKUST−1 [47,48]. It is, therefore, interesting to discover whether the replacement of PLA with another less-hydrophilic thermoplastic polymer as a binding agent could improve the adsorbent moisture stability.…”
Section: Introductionmentioning
confidence: 99%